Ancangan Metodologi Studi Hukum Islam - Imam Amrusi Jailani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
In order to reveal the meaning of the text (nass) of al-Qur’an concerning islamic law, certain interpretation methods are necessary. The urgency of such methodology is related to the issue of the capacity to unearth kegak meaning of al-Qur’an as well as its legal principles. As a result, a person cannot interpret the manig of al-Qur’an carelessly. Moreover, a person cannot claim that his/her interpretation is the only true meaning of al-Qur’an as if he/she is the mouthpiece of God Almighty. An al-Qur’an interpreter (mufassir) can only states that his/her interpretation is the maximum effort of his/her of understanding of al-Qur’an. Nowadays, there are some people of groups who interpret al-Qur’an without mastering interpretation methods of al-Qur’an so that the result is careless interpretation. Therefore, Islamic legal methodology remains crucial.